Role of G protein signaling in the formation of the fibrin(ogen)–integrin αIIbβ3–actin cytoskeleton complex in platelets. (17th August 2016) - Budnik, Ivan; Shenkman, Boris; Savion, Naphtali
Abstract: Effective platelet function requires formation of a physical link between fibrin(ogen), integrin αIIbβ3, and cytoplasmic actin filaments. We investigated the role of the Gαq, Gαi, and Gα12/13 families of heterotrimeric GTP-binding proteins (G proteins) in the assembly of a ligand–αIIbβ3–actin cytoskeleton complex. Selective and combined activation of the G proteins was achieved by using combinations of various platelet agonists and inhibitors. Formation and stability of fibrinogen–αIIbβ3 interaction were evaluated by the extent of platelet aggregation and the rate of eptifibatide-induced platelet disaggregation; association of αIIbβ3 with the cytoskeleton was analyzed by western blot. Formation of the fibrin–αIIbβ3–actin cytoskeleton complex was evaluated by rotational thromboelastometry assay in which clot formation was induced by the mixture of reptilase and factor XIIIa. We demonstrated that involvement of heterotrimeric G proteins in the formation of the ligand–αIIbβ3–cytoskeleton complex depends on whether fibrinogen or fibrin serves as the integrin ligand. Formation of the fibrinogen–αIIbβ3–cytoskeleton complex requires combined activation of at least two G protein pathways while the maximal αIIbβ3–cytoskeleton association and the strongest αIIbβ3–fibrinogen binding supporting irreversible platelet aggregation require combined activation of all three—Gαq, Gαi, and Gα12/13—G protein families. In contrast, formation of the fibrin–αIIbβ3–cytoskeleton complex mediating clot retraction is critically dependent on the activation of the Gαi family, especially on the activation of Gαz.